2009
DOI: 10.1007/s00234-009-0594-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the toxicity of onyx compared with n-butyl 2-cyanoacrylate in the subarachnoid space of a rabbit model: an experimental research

Abstract: This experimental study suggests that NBCA, and various concentrations of onyx and DMSO have toxic effects on the neural tissues of rabbits when infused into the subarachnoid space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Animal studies have shown DMSO itself tends to be angiotoxic and neurotoxic. 18 In the present case, we chose to use Onyx because in our experience it enables a more extensive filling with fewer punctures compared with acrylic glue. Onyx can be injected as slowly as necessary for precise delivery, and the injection can even be stopped to check the degree of embolization and be restarted later.…”
Section: Discussionmentioning
confidence: 97%
“…Animal studies have shown DMSO itself tends to be angiotoxic and neurotoxic. 18 In the present case, we chose to use Onyx because in our experience it enables a more extensive filling with fewer punctures compared with acrylic glue. Onyx can be injected as slowly as necessary for precise delivery, and the injection can even be stopped to check the degree of embolization and be restarted later.…”
Section: Discussionmentioning
confidence: 97%
“…4 Precipitating liquid embolics (eg, ethylene-vinyl alcohol copolymers) was always dissolved in organic solvent (eg, dimethyl-sulfoxide) to perform embolization, but the organic solvent had been reported to induce high toxicity with vascular failure, bleeding, and vascular necrosis in animal experiments. 5,28,29 Another reason for material-related toxicity is attributed to the heat generated during polymerization and release of toxic components (acrylacetate and formaldehyde) for polymerizing liquid embolics (eg, cyanoacrylates). 1,4,5 Unlike these materials, PIB does not need organic solvent in preparation, making it perfect for avoiding the related potential toxicity.…”
Section: Inflammation Reactionsmentioning
confidence: 99%
“…5,28,29 Another reason for material-related toxicity is attributed to the heat generated during polymerization and release of toxic components (acrylacetate and formaldehyde) for polymerizing liquid embolics (eg, cyanoacrylates). 1,4,5 Unlike these materials, PIB does not need organic solvent in preparation, making it perfect for avoiding the related potential toxicity. It is a thermosensitive copolymer and becomes a gelatinous solid at body temperature without releasing heat and toxic components.…”
Section: Inflammation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the clinical application may be problematic in intracranial procedures complicated by the depth of the craniotomy, the high working distances, the tiny spaces, the high angulations, and the cerebrospinal fluid flow. Additionally, the effects of cyanoacrylate on the neural tissues when infused into the subarachnoid space seem to be toxic [19], and more studies should be done to guarantee the safety of the procedure.…”
Section: Discussionmentioning
confidence: 99%